Editorial - Pathan, Al-Sakib Khan; Monowar, Muhammad Mostafa; Alzaid, Hani; Hoque, Mohammad Asadul (Inderscience Publishers, Switzerland, 2015)
Various networking technologies and terms have been coined in the last couple of decades. The dynamism in networking technologies and applications has paved the way for work on multitudes of research areas. While some areas can be broken into more sub-areas and topics, there is a trend among researchers to think about combining different technologies. The term hybrid is commonly used for such case. So, what is the basic difference between the two terms: hybrid and converged? Often people talk about combining the physical structure, or various device platforms, or benefits, or services, or features of different technologies to get a hybrid system. However, the term network convergence or more specifically converged network goes beyond the notion of network hybridisation or hybrid network. In the field of telecommunication, network convergence refers to the provision of telephone, video and data communication services within a single network. So, while hybrid simply refers to combining apparently disjoint technologies/services, convergence refers to the appropriate mixing and smooth functionality of the joint system. That is why a converged network demands one pipe to deliver all forms of communication services.